ATHEROSCLEROTIC EVENT RISK AND RISK REDUCTION THERAPIES AMONG GHANAIAN HEMORRHAGIC STROKE SURVIVORS - Sarfo, Fred Stephen (J Neurol Sci, 2021)
BACKGROUND: Intracerebral hemorrhage (ICH) stroke constitute up to 40% of incident strokes in Africa. While ICH patients are at high risk for atherosclerotic events, the risk-benefit of anti-atherosclerotic therapies in this patient population is uncertain. PURPOSE: To assess whether utility of statins and/ or antithrombotic agents after surviving an ICH correlates with atherosclerotic risk of an observational cohort. METHODS: We analyzed data in a stroke registry prospectively collected on consecutively encountered stroke survivors seen at an out-patient clinic in Ghana between January 2018 and March 2020. We collected baseline demographic and clinical details, including diagnosis of ICH, co-morbidities, and key atherosclerotic risk reduction therapies (statins and anti-platelet drugs). We computed ischemic vascular risk using the Framingham Risk Score (FRS) to classify patients into low, intermediate and high vascular risk. RESULTS: Of 1101 stroke survivors seen during the period, 244 (22.2%) had ICH. Vascular risk profiles were low (n=86; 35.2%), intermediate (n=71; 29.1%) and high (n=87; 35.7%). Utility of statin use was 76.7% (low risk), 84.5% (intermediaterisk), and 87.4% (high risk), p=0.16 while antiplatelet use trended with atherosclerotic risk being 9.3% (low risk), 25.4% (intermediate risk), and high risk (34.5%), p=0.0004. Independent factors associated with statin use were hypertension (OR 8.80; 95% CI: 2.34–33.11) and cigarette smoking (OR 0.29; 95% CI: 0.09–0.89) while antiplatelet drug use was associated with age (OR 1.43; 95% CI: 1.06–1.92) and time from index stroke (OR: 1.02; 95% CI: 1.01–1.02). CONCLUSION: Approximately two-thirds of ICH survivors in this African sample had intermediate to high risk of future atherosclerotic events. Clinical trials on the timing, safety, and efficacy of statins and antiplatelet drugs among ICH survivors could help better guide risk mitigation in this population.